OECD/G20 Two-Pillar Solution: Does It Promote Inter-Nation Equity? - Vita Apriliasari (JURNAL PAJAK INDONESIA, 2022)
International tax reform through Pillar One and Pillar Two aims to address BEPS issues, in addition to the 15 BEPS Actions previously recommended by the OECD and G20. In this regard, the two-pillar solution is expected to bring global tax justice into reality by ensuring MNEs pay a fair share of taxes. Within an international context, redistribution through achieving inter-nation equity is as crucial as the other aspects of equity despite the little attention received. Therefore, this study seeks to investigate whether the two-pillar solution promotes inter-nation equity. Based on the analysis of the entitlement approach and the differentiation approach, Pillar One seems to contribute better to the inter-nation equity than Pillar Two. However, the complexities surrounding Pillar One are likely to set back its positive impact. Meanwhile, a lot more efforts are needed to direct Pillar Two closer to inter-nation equity, having regard to the relatively more benefit of it for developed countries than the developing ones.